Campylobacter spp Gastroenteritis in Paediatric Patients of a Portuguese Hospital: Impact of the COVID-19 Pandemic - De Beir, Joana; Caniço, Joana; Mesquita, Marta; Almeida, Silvia (BIRTH AND GROWTH MEDICAL JOURNAL, 2025)
Introduction: Campylobacter spp is the main cause of acute bacterial gastroenteritis. This study aims to characterise cases of Campylobacter spp acute gastroenteritis (CAG) over the past 10 years in a Portuguese hospital setting and to assess the impact of the COVID-19 pandemic on the incidence and management of these infections. Methods Observational descriptive study of CAG in a Portuguese Paediatrics Department, from 01. June.2013 to 31. December.2023. Diagnosis was established by stool culture/molecular methods. Results: Among 3391 stool samples analysed, 766 tested positive, and Campylobacter spp was isolated in 582 of them. A total of 502 CAG were diagnosed: 89% caused by C. jejuni, 63% were male, and the median age was 2 years. Co-infections were found in 12% of the cases. The incidence of CAG increased over the years, mainly after the emergence of the COVID-19 pandemic. Conclusions: Over the last 10 years, there has been an increase of CAG, mainly affecting young children and boys. After COVID-19, the incidence of campylobacteriosis increased, for reasons that remain to be clarified. Although the clinical course was mostly benign, the acute complications raised after the pandemic.